Intravoxel Incoherent Motion Magnetic Resonance Imaging in Partially Nephrectomized Kidneys. Issue 5 (May 2016) - Schneider, Moritz Jörg; Dietrich, Olaf; Ingrisch, Michael; Helck, Andreas; Winter, Katharina Stella; Reiser, Maximilian F.; Staehler, Michael; Casuscelli, Jozefina; Notohamiprodjo, Mike
Abstract : Objective: The aim of this study was to investigate the effects of partial nephrectomy (PN) in kidneys with solid renal masses on the apparent diffusion coefficient (ADC) and on intravoxel incoherent motion (IVIM)–based parameters using diffusion-weighted magnetic resonance imaging (DWI). Methods: Fifteen patients with renal masses underwent DWI before and 1 week after PN on a clinical 3 T scanner using a single-shot echo planar imaging sequence with 10 diffusion weightings. Motion-corrected images were quantified using a monoexponential model fit to calculate ADCs and a segmented biexponential fit to calculate IVIM parameters f (perfusion fraction), D slow and D fast ("slow" and "fast" diffusion coefficients), as well as the pseudoflow ( PF ) D fast × f . The median values derived from multislice (minimum of 3 slices) regions of interest encompassing the kidney cortex were used for statistical analysis. Estimated glomerular filtration rate values were calculated based on serum creatinine levels on each examination day using the Modification of Diet in Renal Disease formula. Results: The follow-up measurement yielded significantly lower values in the partially nephrectomized kidneys compared with contralateral kidneys for the parameters ADC ( P = 0.002), D fast ( P = 0.43), f ( P = 0.001), and PF ( P = 0.0008). Comparing baseline and follow-up, partially nephrectomized kidneys showed a significant decrease for ADC ( P = 0.01), D fast ( P = 0.43), f ( P = 0.002), and PF ( P = 0.002). Nonnephrectomized kidneys expressed a significant increase for ADC ( P = 0.01) and PF ( P = 0.01). Follow-up Modification of Diet in Renal Disease showed positive correlations with all DWI parameters in the partially nephrectomized kidneys (ADC: r 2 = 0.63, P = 0.0004; D fast : r 2 = 0.59, P = 0.0009; f : r 2 = 0.36, P = 0.018; PF : r 2 = 0.60, P = 0.00075) except for D slow . Conclusions: Our study suggests that quantitative parameters derived from DWI are highly indicative of renal function. Apparent diffusion coefficients showed substantial differences in the renal cortex after PN, whereas an IVIM analysis delivered additional insight into kidney physiology. Quantitative DWI, particularly perfusion-related IVIM parameters, therefore demonstrated great potential as truly noninvasive biomarker to obtain information about single kidney function. Abstract : Supplemental digital content is available in the text.